Dead to me. Season one [videorecording (DVD)] - Feldman, Liz (Paramount, 2020)
Dead to Me stars Christina Applegate as Jen, a poised and put together woman with a dark sense of humor and an anger problem that she doesn't necessarily want to deal with. Jen has been struggling to keep it together in the months since her husband was killed in a hit-and-run accident. When she joins a grief support group she meets Judy (Linda Cardellini), a free spirit with a shocking secret.